2015
DOI: 10.22265/acnef.2.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of graftpost- transplant renal survival

Abstract: ResumenIntroducción: Los pacientes post trasplante renal presentan una Supervivencia media inferior a la de población general, esta supervivencia se disminuye más cuando está relacionada con pérdida del injerto; se pretende identificar la contribución de los factores de riesgo con la pérdida del injerto. Materiales y métodos:Estudio de Cohorte retrospectiva post-trasplante renal; se describieron las características generales de los pacientes; se calculó el RR (Riesgo relativo) para el riesgo de pérdida del inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are some survival and mortality studies with similar results 15,19 . Nevertheless, these studies express their final data in frequencies and percentage, with smaller populations than the one we studied, with 164 and 184 patients compared to the 1118 transplanted from ours 19,29 . Our study did not analyze other factors strongly related with the deceased donor, such as cold ischemia or having extended or expanded criteria for death.…”
Section: Discussionmentioning
confidence: 94%
“…There are some survival and mortality studies with similar results 15,19 . Nevertheless, these studies express their final data in frequencies and percentage, with smaller populations than the one we studied, with 164 and 184 patients compared to the 1118 transplanted from ours 19,29 . Our study did not analyze other factors strongly related with the deceased donor, such as cold ischemia or having extended or expanded criteria for death.…”
Section: Discussionmentioning
confidence: 94%
“…The 5-year graft survival was 77.0%, 72.9%, 71.3% and 62.5%, respectively, und the 10-year graft survival was 56.5%, 48.2%, 45.7% and 33.7%, respectively 12 . For example, in Columbian study in the 164 patients with renal transplantation, patient survival at 5 years was 92.1%, but graft survival at 5 years was 88.4% 1 . The 20-year patient survival rates were 37%, but graft survival rate was 13% 13 .Wang et al was shown that 5-year patient survival with deceased-donor in US, Australia and New Zealand, and Europe was 86.1%, 90%, and 87.1%, respectively 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease is an important health problem worldwide, since it is associated with increased risk of morbidity and mortality in this large group of population 1 . Renal transplantation is the best and preferred way of treating patients with end-stage renal disease, as it offers improved survival and better quality of life in comparison to dialysis 2,3 .…”
Section: Introductionmentioning
confidence: 99%